Seasonal variation of diarrhoeal pathogens among Guinea-Bissauan children under five years of age. - Sointu Mero; Tinja Lääveri; Johan Ursing; Lars Rombo; Poul-Erik Kofoed; Anu Kantele (Public Library of Science (PLoS), 2023)
Background Diarrhoea remains a major cause of childhood morbidity and mortality in low-income countries (LICs). The frequency of diarrhoeal episodes may vary by season, yet few prospective cohort studies have examined seasonal variation among various diarrhoeal pathogens using multiplex qPCR to analyse bacterial, viral and parasitic pathogens. Methods We combined our recent qPCR data of diarrhoeal pathogens (nine bacterial, five viral and four parasitic) among Guinea-Bissauan children under five years old with individual background data, dividing by season. The associations of season (dry winter and rainy summer) and the various pathogens were explored among infants (0-11 months) and young children (12-59 months) and those with and without diarrhoea. Results Many bacterial pathogens, especially EAEC, ETEC and Campylobacter, and parasitic Cryptosporidium, prevailed in the rainy season, whereas many viruses, particularly the adenovirus, astrovirus and rotavirus proved common in the dry season. Noroviruses were found constantly throughout the year. Seasonal variation was observed in both age groups. Conclusion In childhood diarrhoea in a West African LIC, seasonal variation appears to favour EAEC, ETEC, and Cryptosporidium in the rainy and viral pathogens in the dry season.